2015
DOI: 10.1016/j.cortex.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Distinct loci of lexical and semantic access deficits in aphasia: Evidence from voxel-based lesion-symptom mapping and diffusion tensor imaging

Abstract: Please cite this article as: Harvey DY, Schnur TT, Distinct loci of lexical and semantic access deficits in aphasia: Evidence from voxel-based lesion-symptom mapping and diffusion tensor imaging, CORTEX (2015), doi: 10.1016/j.cortex.2015.03.004. This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
98
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(109 citation statements)
references
References 128 publications
(182 reference statements)
10
98
0
1
Order By: Relevance
“…4). This corroborates findings from previous studies that have implicated damage to the WM underlying the posterior temporal lobe in language deficits that span broad domains of language function (Baldo et al, 2013, Bonilha et al, 2015, Butler et al, 2014, Dronkers et al, 2004, Fridriksson, 2010, Fridriksson et al, 2013, Geva et al, 2012, Harvey and Schnur, 2015, Henseler et al, 2014, Ivanova et al, 2016). This region contains fibers associated with both dorsal (AF) and ventral (ILF and IFOF) language processing streams that support integrated sensorimotor language processing and the extraction of meaning from auditory language, respectively (KĂŒmmerer et al, 2013, Saur et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…4). This corroborates findings from previous studies that have implicated damage to the WM underlying the posterior temporal lobe in language deficits that span broad domains of language function (Baldo et al, 2013, Bonilha et al, 2015, Butler et al, 2014, Dronkers et al, 2004, Fridriksson, 2010, Fridriksson et al, 2013, Geva et al, 2012, Harvey and Schnur, 2015, Henseler et al, 2014, Ivanova et al, 2016). This region contains fibers associated with both dorsal (AF) and ventral (ILF and IFOF) language processing streams that support integrated sensorimotor language processing and the extraction of meaning from auditory language, respectively (KĂŒmmerer et al, 2013, Saur et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…Damage to the WM underlying the left posterior superior and middle temporal gyri (pSTG and pMTG) has been consistently implicated as a source of deficits in multiple language domains including comprehension (Dronkers et al, 2004, Geva et al, 2012, Henseler et al, 2014, Pustina et al, 2016, Yourganov et al, 2016), naming (Baldo et al, 2013, Harvey and Schnur, 2015, Henseler et al, 2014, Pustina et al, 2016, Yourganov et al, 2016), repetition (Butler et al, 2014, Henseler et al, 2014, Pustina et al, 2016, Yourganov et al, 2016), and phonology (Butler et al, 2014). The presence of lesions affecting the posterior temporal WM and disrupting posterior temporal connectivity also predicts poor responses to language therapies (Bonilha et al, 2015, Fridriksson, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These findings support the phonological hypothesis and the long-standing theory of WA that language comprehension is impaired because poor quality phonological analysis of the speech stream has a downstream impact on semantic access and analysis (Luria, 1976;Luria & Hutton, 1977). Consistent with this hypothesis all the WA aphasia participants also displayed a lesion to the superior temporal sulcus, a region associated with phonological analysis (DeWitt & Rauschecker, 2012;Harvey & Schnur, 2015;Humphries, Binder et al, 2007;Indefrey & Levelt, 2004;Krieger-Redwood & Jefferies, 2014;Saur, Schelter et al, 2010). This hypothesis was further examined in the control population by artificially degrading the speech input using Saberi speech.…”
Section: Individuals With Wa Judged Congruent Phonologically Incongrsupporting
confidence: 77%
“…All WA participants displayed a lesion affecting the middle temporal gyrus, a region associated with semantic processing (DeWitt & Rauschecker, 2012;Harvey & Schnur, 2015;Humphries, Binder et al, 2007;Indefrey & Levelt, 2004;Krieger-Redwood & Jefferies, 2014;Saur, Schelter et al, 2010) and seen to be modulated by the same experimental features as the N400 in functional imaging experiments (Lau, Phillips et al, 2008). Supporting the semantic hypothesis, greater N400 effects were identified in the WA group when semantic incongruency judgments were easier.…”
Section: Individuals With Wa Judged Congruent Phonologically Incongrmentioning
confidence: 58%
“…However, in terms of permanent deficits, because DES-elicited errors constitute the stopping point for oncological resections, any postoperative language deficits are typically transient and difficult to attribute uniquely to IFOF damage. Yet recently, a preliminary voxel-based lesion mapping study in stroke patients found semantic naming deficits to associate with IFOF damage 29. Neurological studies suggest that IFOF fibres may additionally contribute to aspects of face processing, although evidence of selective face recognition deficits associated with oncological damage is currently lacking.…”
Section: Relevance Of White Matter In Neuro-oncological Treatmentmentioning
confidence: 99%